2006
DOI: 10.1111/j.1365-2257.2006.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of large B cell lymphoma: a case report and review of literature

Abstract: Diffuse large B cell lymphoma (DLBCL) is the largest subtype of non-Hodgkin's lymphomas (NHLs) and is characterized by relatively frequent extranodal presentation. In these cases, the most common extranodal localizations are stomach, CNS, bone, testis and liver. Simultaneous detection of multiple extranodal involvement at presentation is quite uncommon, with the majority of these cases characterized by gastric or intestinal disease localization. Retrospective analysis concerning multifocal extranodal NHLs neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…This form accounts for one-third of all NHL cases (1). Diffuse large B-cell lymphoma (DLBCL) is the predominant type of NHL, accounting for approximately 40% of all lymphomas (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This form accounts for one-third of all NHL cases (1). Diffuse large B-cell lymphoma (DLBCL) is the predominant type of NHL, accounting for approximately 40% of all lymphomas (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse large B-cell lymphoma (DLBCL) is the predominant type of NHL, accounting for approximately 40% of all lymphomas (2,3). It has also been reported that 30-50% of NHL cases have extranodal manifestations in various organs, such as the gastric tract, skin, bone, central nervous system, breast, heart, liver, or adrenal glands (1).…”
Section: Introductionmentioning
confidence: 99%
“…Other sites commonly involved include the skin, CNS, thyroid and lung,7 but disease is usually restricted to a single anatomical site, indicating organ-specific lymphoid proliferation or migration. A small proportion of patients may show multifocal extranodal lymphoma at diagnosis, but, to our knowledge, simultaneous involvement of no more than three extranodal sites has previously been described 7 – 9.…”
Section: Discussionmentioning
confidence: 99%
“…Other sites commonly involved include the skin, CNS, thyroid and lung,7 but disease is usually restricted to a single anatomical site, indicating organ-specific lymphoid proliferation or migration. A small proportion of patients may show multifocal extranodal lymphoma at diagnosis, but, to our knowledge, simultaneous involvement of no more than three extranodal sites has previously been described 7 – 9. This report on the occurrence of likely diffuse large B-cell lymphoma in six extranodal sites including kidneys, adrenals, lungs, liver and pancreas, with a possible low-grade lymphomatous infiltrate in the bone marrow, without significant nodal disease is therefore unusual.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, the origin of primary extranodal NHL can be ascribed to one given organ system or site, with most common extranodal sites being the stomach, skin, and small intestine. The breast, thyroid, lung, heart, liver, genitourinary tract, adrenal glands and bone could also be primarily affected [1].…”
Section: Introductionmentioning
confidence: 99%